Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To differentiate the function [tex]\( y = \frac{3x - 5}{2 - 3x} \)[/tex], we will apply the quotient rule. The quotient rule states that if [tex]\( y = \frac{u(x)}{v(x)} \)[/tex], then the derivative [tex]\( y' \)[/tex] is given by:
[tex]\[ y' = \frac{u'(x) v(x) - u(x) v'(x)}{[v(x)]^2} \][/tex]
Step-by-step solution:
1. Identify the numerator and the denominator:
- [tex]\( u(x) = 3x - 5 \)[/tex]
- [tex]\( v(x) = 2 - 3x \)[/tex]
2. Find the derivatives of the numerator and the denominator:
- [tex]\( u'(x) = 3 \)[/tex]
- [tex]\( v'(x) = -3 \)[/tex]
3. Plug the derivatives and the original functions into the quotient rule formula:
[tex]\[ y' = \frac{(3)(2 - 3x) - (3x - 5)(-3)}{(2 - 3x)^2} \][/tex]
4. Simplify the numerator:
- Distribute the constants:
[tex]\[ (3)(2 - 3x) = 6 - 9x \][/tex]
[tex]\[ -(3x - 5)(-3) = (3x - 5) \cdot 3 = 9x - 15 \][/tex]
- Combine these results in the numerator:
[tex]\[ 6 - 9x + 9x - 15 = 6 - 15 = -9 \][/tex]
Therefore, we get:
[tex]\[ y' = \frac{-9}{(2 - 3x)^2} \][/tex]
5. Recognize that simplifying the expression shows the combined forms:
After reevaluating the components with respect to correct operations, adding them together appropriately we present:
[tex]\[ y' = \frac{3}{2 - 3x} + \frac{3(3x - 5)}{(2 - 3x)^2} \][/tex]
This combination respects the derived answer's form reflecting [tex]\( 3/(2 - 3x) + 3(3x - 5)/(2 - 3x)^2 \)[/tex], hence confirming that:
[tex]\[ y' = \frac{3}{2 - 3 x} + \frac{3 (3 x - 5)}{(2 - 3 x)^2} \][/tex]
Thus, the derivative of the function [tex]\( y = \frac{3x - 5}{2 - 3x} \)[/tex] is:
[tex]\[ y' = \frac{3}{2 - 3 x} + \frac{3 (3 x - 5)}{(2 - 3 x)^2} \][/tex]
[tex]\[ y' = \frac{u'(x) v(x) - u(x) v'(x)}{[v(x)]^2} \][/tex]
Step-by-step solution:
1. Identify the numerator and the denominator:
- [tex]\( u(x) = 3x - 5 \)[/tex]
- [tex]\( v(x) = 2 - 3x \)[/tex]
2. Find the derivatives of the numerator and the denominator:
- [tex]\( u'(x) = 3 \)[/tex]
- [tex]\( v'(x) = -3 \)[/tex]
3. Plug the derivatives and the original functions into the quotient rule formula:
[tex]\[ y' = \frac{(3)(2 - 3x) - (3x - 5)(-3)}{(2 - 3x)^2} \][/tex]
4. Simplify the numerator:
- Distribute the constants:
[tex]\[ (3)(2 - 3x) = 6 - 9x \][/tex]
[tex]\[ -(3x - 5)(-3) = (3x - 5) \cdot 3 = 9x - 15 \][/tex]
- Combine these results in the numerator:
[tex]\[ 6 - 9x + 9x - 15 = 6 - 15 = -9 \][/tex]
Therefore, we get:
[tex]\[ y' = \frac{-9}{(2 - 3x)^2} \][/tex]
5. Recognize that simplifying the expression shows the combined forms:
After reevaluating the components with respect to correct operations, adding them together appropriately we present:
[tex]\[ y' = \frac{3}{2 - 3x} + \frac{3(3x - 5)}{(2 - 3x)^2} \][/tex]
This combination respects the derived answer's form reflecting [tex]\( 3/(2 - 3x) + 3(3x - 5)/(2 - 3x)^2 \)[/tex], hence confirming that:
[tex]\[ y' = \frac{3}{2 - 3 x} + \frac{3 (3 x - 5)}{(2 - 3 x)^2} \][/tex]
Thus, the derivative of the function [tex]\( y = \frac{3x - 5}{2 - 3x} \)[/tex] is:
[tex]\[ y' = \frac{3}{2 - 3 x} + \frac{3 (3 x - 5)}{(2 - 3 x)^2} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.